Face strategies in headlines from the Nigerian tribune's court and crime column - Jegede, Olusegun Oladele (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2024)
This study conducts an in-depth analysis of face-saving and face-threatening acts as depicted in selected headlines sourced from the Court and Crime Column in the Nigerian Tribune, with a specific focus on the context of marital relationships. Employing a qualitative content analysis, the research looks into the intricate elements of language and communication strategies employed by individuals within these headlines. The findings elucidated both face-saving and face-threatening acts, illuminating the many dynamics inherent in marital communication. Through careful examination, key themes emerged, encompassing a spectrum of behaviour including accusations, justifications, denials, and endeavours aimed at preserving one's reputation. By shedding light on these underlying patterns, the study underscores the crucial role of language and communication in marital relationships, offering valuable insights into the strategies individuals employ to safeguard their own dignity or challenge the integrity of their partners. Moreover, the research contributes significantly to our understanding of the complexities surrounding communication dynamics within marriages, emphasizing the profound impact of face-saving and face-threatening acts on perceptions and relationship outcomes. Ultimately, the study advocates for the adoption of effective communication strategies, emphasizing the importance of positive language choices, empathy, and understanding as fundamental pillars for fostering and sustaining healthy and harmonious marital relationships.